N2+-implantation-induced tailoring of structural, morphological, optical, and electrical characteristics of sputtered molybdenum thin films - Rani, Usha; Devi, Kafi; Gupta, Divya; Aggarwal, Sanjeev (Beilstein Journal of Nanotechnology, 2025)
Molybdenum (Mo) thin films have extensive applications in energy storage devices and photovoltaic solar cells because of their remarkable thermal stability, high melting point, and chemical inertness. In the present study, Mo thin films of different thicknesses (150, 200, 250, and 300 nm) have been deposited on Si(100) substrates via radio frequency sputtering in an argon atmosphere at room temperature. Some of these films have been implanted with 1 × 1017 N2+·cm−2 at 30 keV using a current density of 4 µA·cm−2. Surface morphology and structural, optical, and electrical properties of the as-deposited and implanted Mo thin films have been systematically investigated. The crystallinity of Mo thin films is enhanced with increasing thickness of the as-deposited films. This pattern persists with film thickness even after N2+ implantation. After implantation, crystallinity decreases relative to as-deposited films with the same nominal thickness. The AFM analysis reveals that RMS roughness increases with the thickness of Mo films. Optical studies using spectroscopic ellipsometry reveal a significant increase in absorbance and reflectance in as-deposited and N2+-implanted films. Electrical investigations show that the conductivity increases with film thickness in both as-deposited and implanted films. The conductivity decreases for the same nominal film thickness after implantation.
Keywords: atomic force microscopy; grazing angle X-ray diffractometer; Keithley parametric analyzer; Mo thin films; RF sputtering; spectroscopic ellipsometry